MP-10 Subcloning Gene Encoding Rophtry 1 (ROP1) Toxoplasma gondii WTA Isolate - Purmaningtyas Kusumaningsih; W T Artama; S Moeljoparwiro (Hemera Zoa, 2018)
Toxoplasma gondii is an obligate intracellular parasite which could infected all organism, and built a vacuola parasitoporus for multiplicity their self in host [1]. Toxoplasmosis is the one of zoonotic diseases which could infected animal and human and involved that two organism to their life [2].Toxoplasmosis in animal is difficult to held, it cause involved the environment. Oosit could sporulated in the water, it made fish, walrus and other mamalian infected by T. gondii. Bat could be a vector of T. gondii if they bite cattle where in it bloods contain with tachyzoites [3]. Toxoplasmosis in ranch such as cattle, pork, sheep, goat and poultry focused on reproduction health that impact economics system and causes congenital disease. This condition can impact for fulfill of prime seed and good meat for human consumption [4].The invasion of T. gondii to host cell could cause immunology reaction like cytokine secretors such as IL-12, IFN-γ, TNF-α and T cells such as CD4+ and CD8+. It involved surface antigen/SAG protein and excretory-secretory antigen/ESA protein [5].Rophtry-1 protein has functioned as a penetration factor and it has 66 kDa molecular of weight. Cloning gene of rophtry-1 T. gondii RH isolate have done and result on vaccination using recombinant plasmid rop1, improving activity of natural kill cells, cell and T proliferation. Recombinant antigen of ROP1 also can use for toxoplasma diagnosis [6,7].The aim of these studies was to sub-clone the gene encoding ROP-1 protein T. gondii WTA isolate to pET-32a(+) and produced a recombinant plasmid of ROP-1 in E. coli BL-21(DE3). This recombinant plasmid will be used to produce a recombinant protein which will be able to perform preliminary studies on its stability on detect T. gondii specific antibodies.